Analytic induction for social research - Ragin, Charles C (University of California Press, 2023)
This book explores analytic induction, an approach to the analysis of cross-case evidence on qualitative outcomes that has deep roots in sociology. A popular research technique in the early decades of empirical sociology, analytic induction differs fundamentally as a method of social research from conventional variation-based approaches. In Analytic Induction for Social Research, Charles C. Ragin demonstrates that much is gained from systematizing analytic induction. The approach he introduces here offers a new template for conducting cross-case analysis and provides a new set of tools for answering common research questions that existing methods cannot address. “Breaks new ground in introducing analytic induction as an approach distinct from qualitative comparative analysis. Charles Ragin’s writing is among the clearest, most accessible, and engaging that I know.” — PEER C. FISS, Jill and Frank Fertitta Chair in Business Administration and Professor of Management and Organization, University of Southern California “At a time when methodological debates are becoming increasingly mathematical, this intervention is both refreshingly nontechnical and unusually helpful for qualitative researchers in sociology and political science. Because of its clarity, brevity, and usability, qualitative researchers in the social sciences are going to want a copy of this book.” — JAMES MAHONEY, Gordon Fulcher Professor in Decision-Making and Professor of Sociology and Political Science, Northwestern University